Perspectives on solar geoengineering from Finnish Lapland: Local insights on the global imaginary of Arctic geoengineering. Issue 91 (May 2018) - Buck, Holly Jean
Highlights: Few studies explore Arctic perspectives on Arctic geoengineering. Uses semi-structured interviews to explore Laplander ideas of solar geoengineering. Affective concerns about loss, insecurity, and uncanny climates. Concerns informed by Arctic and contextual histories. Respondents question whether states will make decisions in their interest. Abstract: "Solar geoengineering" or albedo modification—changing the reflectivity of the earth, using methods like placing particles in the stratosphere—has been proposed as a means to potentially cool the Arctic and forestall climate tipping points. However, this concept has remained a global imaginary, grounded in coarse-resolution climate modeling. How do people actually living in the Arctic imagine themselves experiencing or shaping solar geoengineering? How can the experience of people in particular places inform discussions of solar geoengineering governance? This paper synthesizes perspectives from extended interviews with citizen stakeholders in Finnish Lapland. Rather than approaching solar geoengineering from the perspective of Arctic or local interests, respondents took a global view of its prospects and governance. However, the idea of solar geoengineering also sparked deeper discussions about northern or Arctic ways of living in the Anthropocene: how to coexist with loss and unfamiliar climates, relocalization and new rural livelihoods in the north, and dematerialization of northern economies. The results challenge some common tacit assumptions in geoengineering governance discourse: (1) that people's climate preferences are obvious or quantifiable; (2) that individuals will look at solar geoengineering through an personal, utilitarian lens, or as a game of maximizing benefits to their region, when in fact they may have a cosmopolitan or interconnected systems-perspective; and (3) that states act in the interests of their citizens, when in fact they may act in the interests of elites.